Towards understanding of laccase-catalysed oxidative oligomerisation of dimeric lignin model compounds. Issue 20 (20th February 2017) - Ramalingam, B.; Sana, B.; Seayad, J.; Ghadessy, F. J.; Sullivan, M. B.
Abstract : The isolation of early intermediates in the laccase-catalysed oligomerisation of lignin model compounds indicated the preferential formation of C5 –C5′ over C5 –O–C4′ linkages. Abstract : Laccase-catalysed oligomerisation of dimeric β-O-4 linked lignin model compounds was studied in detail to understand the oligomerisation process by monitoring the reaction progress using high performance liquid chromatography (HPLC) and mass spectroscopy (MS). The initial oxidation intermediates of oligomerisation were isolated for the first time and characterised by spectroscopic methods sucessfully. The experimental observations indicated that C5 –C5′ biphenyl linkages, one of the most thermodynamically stable linkages present in the native lignin, are formed exclusively during the early stage of the oligomerisation process. The experimental observations were supported by density functional theory (DFT) calculations of relative free energies of possible products. The C5 –C5′ biphenyl tetramer is the thermodynamically more favoured product compared to the C5 –O–C4′ product by a free energy difference of 10.0 kcal mol −1 in water. Among the various linking possibilities for further formation of hexamers, the thermodynamically more stable product with a similar C–C linkage is proposed as a plausible structure based on the mass of the hexamer isolated and DFT calculations. The current study demonstrates that laccase catalyzes the oligomerisation more preferentially than oxidative bond cleavage in β-O-4 linkages and that product formation is likely controlled by the thermodynamic stability of the resultant oligomers.